Semi-automated Detection of the Timing of Respiratory Muscle Activity: Validation and First Application - Rodrigues, Antenor; Janssens, Luc; Langer, Daniel; Matsumura, Umi; Rozenberg, Dmitry; Brochard, Laurent; Reid, W. Darlene (Frontiers in Physiology, 2022)
Background: Respiratory muscle electromyography (EMG) can identify whether a muscle is activated, its activation amplitude, and timing. Most studies have focused on the activation amplitude, while differences in timing and duration of activity have been less investigated. Detection of the timing of respiratory muscle activity is typically based on the visual inspection of the EMG signal. This method is time-consuming and prone to subjective interpretation. Aims: Our main objective was to develop and validate a method to assess the respective timing of different respiratory muscle activity in an objective and semi-automated manner. Method: Seven healthy adults performed an inspiratory threshold loading (ITL) test at 50% of their maximum inspiratory pressure until task failure. Surface EMG recordings of the costal diaphragm/intercostals, scalene, parasternal intercostals and sternocleidomastoid were obtained during ITL. We developed a semi-automated algorithm to detect the onset (EMG,onset) and offset (EMG,offset) of each muscle's EMG activity breath-by-breath with millisecond accuracy and compared its performance with manual evaluations from two independent assessors. For each muscle, the Intraclass Coefficient correlation (ICC) of the EMG,onset detection was determined between assessors and between the algorithm and each assessor. Additionally, we explored muscle differences in the EMG,onset and EMG,offset timing and duration of activity throughout the ITL. Results: More than 2000 EMG,onsets were analyzed for algorithm validation. ICCs ranged from 0.75-0.90 between assessor 1 and 2, 0.68-0.96 between assessor 1 and the algorithm and 0.75-0.91 between assessor 2 and the algorithm (P<0.01 for all). The lowest ICC was shown for the diaphragm/intercostal (0.68) and the highest for the parasternal intercostal (0.96). During ITL, diaphragm/intercostal EMG,onset occurred later during the inspiratory cycle and its activity duration was shorter than the scalene, parasternal intercostal and sternocleidomastoid (P<0.01). EMG,offset occurred synchronously across all muscles (P≥0.98). EMG,onset and EMG,offset timing and activity duration was consistent throughout the ITL for all muscles (P>0.63). Conclusion: We developed an algorithm to detect EMG,onset of several respiratory muscles with millisecond accuracy that is time-efficient and validated against manual measures. Compared to the inherent bias of manual measures, the algorithm enhances objectivity and provides a strong standard for determining the respiratory muscle EMG,onset.